Fabry disease exacerbates renal interstitial fibrosis after unilateral ureteral obstruction via impaired autophagy and enhanced apoptosis - Sungjin Chung; Mina Son; Yura Chae; Songhee Oh; Eun Sil Koh; Yong Kyun Kim; Seok Joon Shin; Cheol Whee Park; Sung-Chul Jung; Ho-Shik Kim (The Korean Society of Nephrology, 2021)
Background Fabry disease is a rare X-linked genetic lysosomal disorder caused by mutations in the GLA gene encoding alpha-galactosidase A. Despite some data showing that profibrotic and proinflammatory cytokines and oxidative stress could be involved in Fabry disease-related renal injury, the pathogenic link between metabolic derangement within cells and renal injury remains unclear. Methods Renal fibrosis was triggered by unilateral ureteral obstruction (UUO) in mice with Fabry disease to investigate the pathogenic mechanism leading to fibrosis in diseased kidneys. Results Compared to kidneys of wild-type mice, lamellar inclusion bodies were recognized in proximal tubules of mice with Fabry disease. Sirius red and trichrome staining revealed significantly increased fibrosis in all UUO kidneys, though it was more prominent in obstructed Fabry kidneys. Renal messenger RNA levels of inflammatory cytokines and profibrotic factors were increased in all UUO kidneys compared to sham-operated kidneys but were not significantly different between UUO control and UUO Fabry mice. Protein levels of Nox2, Nox4, NQO1, catalase, SOD1, SOD2, and Nrf2 were not significantly different between UUO control and UUO Fabry kidneys, while the protein contents of LC3-II and LC3-I and expression of Beclin1 were significantly decreased in UUO kidneys of Fabry disease mouse models compared with wild-type mice. Notably, TUNEL-positive cells were elevated in obstructed kidneys of Fabry disease mice compared to wild-type control and UUO mice. Conclusion These findings suggest that impaired autophagy and enhanced apoptosis are probable mechanisms involved in enhanced renal fibrosis under the stimulus of UUO in Fabry disease.